2014
DOI: 10.1177/2333794x14561289
|View full text |Cite
|
Sign up to set email alerts
|

American and Brazilian Children With Primary Urolithiasis

Abstract: Objectives. Considering the differences in location, socioeconomic background, and cultural background, the aim of this study was to try to identify possible factors associated with the increased incidence of urolithiasis by comparing American and Brazilian children with stones. Methods. Data of 222 American and 190 Brazilian children with urolithiasis were reviewed including age, gender, body mass index, imaging technique used (ultrasound and computed tomography), and 24-hour urine volume and chemistries. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 31 publications
3
4
0
Order By: Relevance
“…Most patients were male, in agreement with the findings of other investigations 17 ( Table 2 ). While it is historically more frequent in this sex, 1 the incidence of UL among the female population is already higher in some studies.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Most patients were male, in agreement with the findings of other investigations 17 ( Table 2 ). While it is historically more frequent in this sex, 1 the incidence of UL among the female population is already higher in some studies.…”
Section: Discussionsupporting
confidence: 92%
“…Conversely, other studies showed a variation of 11.3–11.8 years old, a higher average than that observed in the present study. 18 , 20 This lower age at the diagnosis of the Brazilian patients was already verified by Penido et al 17 in a cohort study with American and Brazilian children and adolescents with UL. The authors showed that the Brazilian patients are usually younger at the diagnosis.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…Kovacevic et al 23 pointed out to the importance of the association between previous urinary infection and hypocitraturia, and this result was confirmed in this study. In the study by Penido, 24 24.3% of the cases showed no metabolic change, only the reduction in urine volume (normal value: ≥1 ­mL/­kg/h). These findings suggest that the dietary investigation and the urinary metabolic analysis are essential to the follow-up of these patients.…”
Section: Discussionmentioning
confidence: 91%